2017
DOI: 10.1016/j.maturitas.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing menopausal symptoms for women during the menopause transition using group education in a primary health care setting—a randomized controlled trial

Abstract: NTC02852811.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Menopause is a natural process but accompanied with complex changes for women over 50 year-old; menopause, which is considered a turning point, may occur earlier in some women [ 37 , 38 ]. According to the World Health Organization (WHO), an estimated one billion women will be over 60 year-old by the year 2050, suggesting that more than one billion women will be at the postmenopausal status, which is becoming a worldwide concern in public health [ 39 ]. Peri- and post-menopausal women often show multiple menopausal signs and symptoms, among which the most common during menopausal transition are hot flushes, night sweats, recurrent fatigue, and even memory loss and mild depression [ 40 – 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Menopause is a natural process but accompanied with complex changes for women over 50 year-old; menopause, which is considered a turning point, may occur earlier in some women [ 37 , 38 ]. According to the World Health Organization (WHO), an estimated one billion women will be over 60 year-old by the year 2050, suggesting that more than one billion women will be at the postmenopausal status, which is becoming a worldwide concern in public health [ 39 ]. Peri- and post-menopausal women often show multiple menopausal signs and symptoms, among which the most common during menopausal transition are hot flushes, night sweats, recurrent fatigue, and even memory loss and mild depression [ 40 – 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In their study carried out with menopausal women, Patel and Kim et al also found that healthy lifestyle education had a positive effect on reducing the symptoms experienced by menopausal women and on increasing their awareness of menopause 38,39 . Rindner et al conducted a study with 131 menopausal women aged 45-55 years with the aim of reducing the menopausal symptoms in primary health care services, and found that group education for menopausal women was effective in reducing the menopausal symptoms 40 . As a result, it can be said that health promotion education for menopausal women is an effective way to reduce the somatic, psychological, and urogenital menopausal symptoms of women.…”
Section: Discussionmentioning
confidence: 99%
“… 26 It is feasible to implement group education on menopause for women. 27 The use of group interventions to improve memory self-efficacy during menopause warrants continued evaluation. 28 The supportive measures, such as increasing the participation of the elderly in public life through proper preparations to join them and membership in peer groups can be effective too.…”
Section: Discussionmentioning
confidence: 99%